2008
DOI: 10.1186/1475-9276-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Waiting times for elective treatments according to insurance status: A randomized empirical study in Germany

Abstract: Background: Health insurance coverage for all citizens is often considered a requisite for reducing disparities in health care accessibility. In Germany, health insurees are covered either by statutory health insurance (SHI) or private health insurance (PHI). Due to a 20%-35% higher reimbursement of physicians for patients with PHI, it is often claimed that patients with SHI are faced with longer waiting times when it comes to obtaining outpatient appointments. There is little empirical evidence regarding outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 19 publications
7
81
1
8
Order By: Relevance
“…This is sensible because doctors are paid based on the number of treatments, not on the number of visits itself, and receive a higher compensation when they treat privately insured patients. They are time constrained and may thus focus on treating privately insured patients first (Lungen et al, 2008;Jürges, 2009), while spending relatively little time on publicly insured patients (Deveugele et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is sensible because doctors are paid based on the number of treatments, not on the number of visits itself, and receive a higher compensation when they treat privately insured patients. They are time constrained and may thus focus on treating privately insured patients first (Lungen et al, 2008;Jürges, 2009), while spending relatively little time on publicly insured patients (Deveugele et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, doctors have an incentive to treat privately insured patients first, and more intensely, possibly providing better treatment (Jürges, 2009). For example, waiting times for privately insured patients are lower on average (Lungen et al, 2008). This may in turn affect the demand for medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitatively better care is increasingly associated with individual resources or access to private health insurance. In the wider society and the media, responses to the recently published study of the Institute for Health Economics at the University of Cologne (Lungen et al 2008) showed the high sensitivity towards topics concerning the health sector. Lungen et al illustrated that patients with statutory health insurance have to wait about three times longer for an appointment in a specialist practice than clients of private insurance companies.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotally, private health insurance is viewed as superior because for one thing, more innovative and costly -and thus supposedly bettertreatments are covered. Additionally, privately insured individuals are treated preferentially by doctors, which manifests, for example, in waiting times that are significantly lower for privately than for publicly insured individuals (Lungen et al, 2008;Kuchinke et al, 2009). 2 However, whether these superior features of private health insurance actually transfer into better health has been examined only inconclusively so far.…”
Section: Introductionmentioning
confidence: 99%